Total Correction of Tetralogy of Fallot: Effect of Transannular Patch on Early Outcome (Cardiovascular Journal, 2018)
Background: It is arguable whether presence of transannular patch is itself a risk factor for adverse outcome at total correction(repair) of tetralogy of Fallot (TOF).This study intended to compare early outcome of intact pulmonary valve annulus with transannular patching at repair of TOF.Methods: This prospective observational study was conducted from July 2015 to January 2017.40 patients were enrolled in 2 groups- A & B.In group A,14 patients with intact pulmonary valve annulus& in group B, 26 patients with transannular patch. The diameter of pulmonary valve annulus was measured with Hegar dilator and Z value of the measured diameter were calculated from an established published nomogram. Transannular patch was placed if Z value of annular diameter < -3 or post repair operative room right ventricle/left ventricle pressure ratio (P RV/LV)> 0.7.Patients were monitored in the intensive care unit(ICU) and followed up for 3 months following discharge from hospital.Results: Patients of group B were younger and smaller body surface area. There were no significant difference of preoperative variables in terms of peripheral arterial oxygen saturation(SpO2%), haematocrit (%),NYHA functional class, right ventricular hypertrophy, and level & severity of right ventricular out flow tract obstruction. Early out come in terms of duration of ventilation time, inotrope support & ICU stay; post operative morbidity & mortality were more in group B than group A patients. Pulmonary regurgitation & right ventricular dysfunction following transannular patch at repair of TOF plays important role for adverse outcome.Conclusion: Transannular patch is associated with higher morbidity and mortality in total correction of Tetralogy of Fallot.Cardiovasc. j. 2018; 10(2): 194-200